Sustainable and developmental mechanisms of network organizations: Creating environment and time management by adult volunteer workers - Fumie KANZAKI (AAOS Transactions)
This research aimed to analyze of the mechanism for sustainable development of wide-area network organization, from the perspective of fluid human resource management focusing on the spatial movement of volunteers and the time axis. In Japan, recently, a movement to re-evaluate discontinued railways as heritage railway and to utilize them for the preservation of local culture and tourism resources is gaining attention. On the other hand, to preserve and utilize sustainable heritage railway, there are issues such as the financial burden on local governments and the securing of human resources. Therefore, it is necessary to construct a wide-area network organization that cooperates not only with local governments and residents, but also with volunteers who live other areas. This paper considered the necessary requirements for working adults with diverse experiences and specialized knowledge to participate continuously as volunteers. As a result of analyzing the case of the Kosaka Railway Preservation Society, it is conclusion that network organization can achieve sustainable development by coordinating different organizational evolution directions based on a bottom-up approach and time management.